The Effect of Hello English Application on Speaking Ability - Ruhut Febiola Simanjuntak; Atni Prawati; Masyhur Masyhur (Universitas Pahlawan Tuanku Tambusai, 2022)
Technology has received a lot of attention because of its potential to solve learning problems in this modern era. Disinterest and low participation of students in the learning process, encourage teachers to use technology as a medium to increase students' enthusiasm for learning English, especially speaking. This research aims to determine whether Hello English application had a significant impact on speaking ability. Pre-experimental research was employed to conduct this research. The sample of this research consisted of 35 students from class XI MIA 1 at SMAN 3 Padang Sidimpuan. The pretest is used to determine the students' initial speaking ability. The posttest was conducted after the treatment was applied in four meetings utilizing Hello English application as a supporting medium in learning English. The t-test formula was used to analyze the collected data. Based on the findings of this research, the t-count value was 26.727, and the t-table value was 2.032. It denotes the alternative hypothesis (Ha) regarding there is a significant effect of Hello English application on the speaking ability of eleventh-grade students at SMAN 3 Padang Sidimpuan is accepted.